1998
DOI: 10.1038/bjc.1998.705
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral infusion of fluid: estimation of hydraulic conductivity and implications for the delivery of therapeutic agents

Abstract: Summary We have developed a new technique to measure in vivo tumour tissue fluid transport parameters (hydraulic conductivity and compliance) that influence the systemic and intratumoral delivery of therapeutic agents. An infusion needle approximating a point source was constructed to produce a radially symmetrical fluid source in the centre of human tumours in immunodeficient mice. At constant flow, the pressure gradient generated in the tumour by the infusion of fluid (Evans blue-albumin in saline) was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 18 publications
10
81
1
Order By: Relevance
“…This suggests that the slower recovery kinetics observed in this study is more likely to represent repair of damage to microvessels rather than clearance of the injected fluid. Jain and colleagues also noted that using a very slow infusion rate from a single point source, bulk flow was responsible for removal of fluid and reabsorption via blood vessels was minimal in the LS174T xenograft tumour (Boucher et al, 1998). Although the authors suggested that stagnant blood flow in the center of these tumours might be responsible, this result could also be explained if blood vessels were damaged in the region surrounding the infusion needle.…”
Section: Experimental Therapeuticsmentioning
confidence: 68%
“…This suggests that the slower recovery kinetics observed in this study is more likely to represent repair of damage to microvessels rather than clearance of the injected fluid. Jain and colleagues also noted that using a very slow infusion rate from a single point source, bulk flow was responsible for removal of fluid and reabsorption via blood vessels was minimal in the LS174T xenograft tumour (Boucher et al, 1998). Although the authors suggested that stagnant blood flow in the center of these tumours might be responsible, this result could also be explained if blood vessels were damaged in the region surrounding the infusion needle.…”
Section: Experimental Therapeuticsmentioning
confidence: 68%
“…We also observed that the Evans blue -labeled albumin accumulated only in the periphery of tumors if the infusion rate was maintained at 5.0 AL/s, indicating that albumin leaked out through some cracks in these tumors. Crack formation has been reported in previous studies of intratumoral infusion (2,20,21). It is likely to be due to the presence of necrotic regions and blood pools as well as abnormal assembly of extracellular matrix in tumors (22).…”
Section: Resultsmentioning
confidence: 91%
“…25 Hydraulic conductivity studies using intratumoral injection of Evans blue dye into tumor centers have shown that tumors vary in their resistance to fluid flow. 24 This resistance could be relieved using hyaluronase to hydrolyze the ECM, demonstrating that tumoral ECM composition and density influence interstitial pressure. Interestingly, the injected dye did not reabsorb into blood vessels as expected perhaps due to the lack of blood flow observed around the area of injection.…”
Section: The Tumor Vasculaturementioning
confidence: 99%
“…20 The chaotic structure of the vasculature, poor smooth muscle cell/pericyte coverage, and the dysfunctional ability of the endothelium to transport fluid create a high intratumoral pressure that perpetuates difficulties in perfusion of the growing tumor. [23][24][25] Due to the hyperpermeability of tumor vessels and the focal leaks often seen in tumor vessels, blood flow rates are reduced as measured by red blood cell velocity. 20,26 Studies have shown that tumors often have increased interstitial pressure 23 and that they can affect the interstitial pressure of surrounding normal tissue.…”
Section: The Tumor Vasculaturementioning
confidence: 99%